A randomized trial to reduce sugar-sweetened beverage and juice intake in preschool-aged children: description of the Smart Moms intervention trial. (December 2016) - Nezami, Brooke; Lytle, Leslie; Tate, Deborah
Abstract Background Obesity in young children remains a public health concern, and maternal weight is one of the strongest predictors of obesity in early childhood. However, parental adherence in interventions for young children is often low and existing programs have had mixed success. An innovative approach to treatment is needed that increases adherence among mothers and improves weight-related behaviors simultaneously in mothers and children. The objective of the Smart Moms randomized controlled trial (RCT) is to test the efficacy of a 6-month primarily smartphone-delivered program to reduce sugar-sweetened beverage and juice consumption among children ages 3–5 whose mothers are overweight or obese. This paper describes the study design and intervention. Methods/Design Mother-child dyads were eligible if the mother was overweight or obese, owned a smartphone, and if the child was between the ages of 3–5 and consumed 12 oz or more per day of sugar-sweetened beverages (SSBs) and 100 % fruit juice. Participants were randomly assigned to the Smart Moms intervention or a waitlist control group. The intervention consisted of theoretically grounded and evidence-based behavioral strategies delivered through one group session, lessons on a mobile-optimized website, and text messages. Mothers submitted self-monitoring information via text message and received regular tailored feedback emails from interventionists. The primary outcome is change in child SSB and juice consumption and a secondary outcome is change in maternal weight. Discussion This Smart Moms study was designed to determine if a low-burden intervention delivered using mobile methods and targeted towards mothers could be effective at changing child sugar-sweetened beverage intake. Results will indicate if mobile-based methods can be a feasible way to engage mothers in family-based studies and will inform successful strategies to prevent childhood obesity through parent-targeted approaches. Trial registration Clinicaltrials.govNCT02098902 (Registered March 25, 2014).